4x + 6 < 3x - 5 is our given inequality
4x < 3x -11 by subtracting 6 on both sides of the inequality sign
x < -11 by subtracting 3x on both sides.
Thus, x < -11 -- choice D -- is the solution.
Answer:
LCM of 20, 30, and 40
LCM = 120
they would cry together for the first time in 120 minutes.
Answer:
Step-by-step explanation:
xxcSD1EA
Answer:
y=-x+2
Step-by-step explanation:
Y intercept = 2
Slope = -1/1 = 1
y=-1x+2
Simplified
y=-x+2
9514 1404 393
Answer:
(x, y, z) = (-1, 0, -3)
Step-by-step explanation:
We notice that the coefficients of z are such that elimination of the z term from the equations is made easy.
Adding equations 1 and 2:
(2x -3y -2z) +(x +3y +2z) = (4) +(-7)
3x = -3
x = -1
Adding equations 2 and 3:
(x +3y +2z) +(-4x -4y -2z) = (-7) +(10)
-3x -y = 3
Substituting for x, we get ...
(-3)(-1) -y = 3
0 = y . . . . . . . . . . . add y-3 to both sides
Then z can be found from any equation. Substituting for x and y in the second equation gives ...
-1 +2z = -7
2z = -6 . . . . . add 1
z = -3 . . . . . .divide by 2
The solution is (x, y, z) = (-1, 0, -3).